Acupuncture vs. antispasmodics in the treatment of irritable bowel syndrome: An adjusted indirect treatment comparison meta-analysis - Shi, Yun-zhou; Tao, Qing-feng; Qin, Di; Chen, Min; Yu, Shu-guang; Zheng, Hui (Frontiers in Physiology, 2022)
Background: Acupuncture, an important complementary and alternative therapy, has been widely used to treat irritable bowel syndrome (IBS) in clinical practice in China. Although its efficacy was shown in some randomized controlled trials (RCTs), it has rarely been compared with first-line antispasmodics to confirm its effectiveness. We aimed to compare acupuncture with antispasmodics by using an adjusted indirect treatment comparison meta-analysis. Methods: We searched the OVID Medline, Embase, and the Cochrane Central Register of Controlled Trials databases for RCTs that compared acupuncture or antispasmodics with placebo or one of them in the treatment of IBS from inception to March 14, 2022. The primary outcome was the improvement of abdominal pain. The secondary outcomes were the relief of global IBS symptoms and adverse events. The effect size was measured by relative ratio or standardized mean difference (SMD), the data were pooled using a random-effects model, and the effectiveness of treatments were ranked according to their P-scores. Results: Thirty-five RCTs (n=5190) were included. The analysis showed that cimetropium, drotaverine, acupuncture and pinarverium were superior over placebo in relieving abdominal pain; cimetropium (SMD, -3.00[95%CI, -4.47 to -1.53], P-score=0.99) ranked the most effective. In pairwise comparisons, acupuncture had a greater improvement than most antispasmodics except cimetropium and drotaverine in relieving abdominal pain, although the between-group difference was statistically insignificant. In the analysis of continuous outcome in the relief of global IBS, the result showed that pinaverium was more effective (SMD, 1.72 [95%CI, 0.53 to 2.92], P-score=0.90) than placebo. Trimebutine and acupuncture had greater improvements than placebo, but no significant between-group difference was noted. In pairwise comparisons, acupuncture had a significantly higher success rate than pinaverium[SMD, -1.11[95%CI, -1.94 to -0.28] in the relief of global IBS. In the analysis of adverse events, acupuncture had a significantly lower adverse events rate than most of the other treatments. Conclusion: Cimetropium, drotaverine, and acupuncture were superior to placebo in terms of improvement of abdominal pain. Acupuncture was superior to pinaverium in relieving global IBS symptoms, and the adverse events of acupuncture were lower than most antispasmodics.